PENGGUNAAN POTRET ORANG LAIN SEBAGAI MEDIA PROMOSI (TINJAUAN EKONOMI SYARIAH dan UNDANG-UNDANG No 28 Tahun 2014) - Erwan Setyanoor (Al-Ujrah | Jurnal Ekonomi Syariah, 2023)
This study investigates the view of Islamic law and law number 28 of 2014 concering regulations for using other people’s pictures to be used as promotional media and how it should be so that other people’s portraits can be used as promotional media. This research is a litertature reveiw, it shows that it violates several things in islamic business ethics, the commercial use of the people’s portraits violates things such as dishonesty, lack of transparency because they have used other people’s portraits without permission. Indonesia has regulations in the form of law to prohibit this, namely law number 28 of 2014 in the first point violates article 9 number 3 which. If concluded as follows “any person without permission of the creator is not allowed to use the creation for profit”, article 12 everyone is prohibited from using other people’s portraits for commercial use without permission from the person being photographed or their heirs. Based on some of the previous things, the outhors draw the conclusion that there is harmonization between law in Indonesia and the Islamic economy, namely providing protection for one’s rights.